2016
DOI: 10.1088/0741-3335/58/11/115009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ideal kink stability in two reactor-relevant tokamak plasma configurations with negative and positive triangularity

Abstract: The effects of an ideal/resistive conducting wall, the drift kinetic resonances, as well as the toroidal plasma flow, on the stability of the ideal external kink mode are numerically investigated for a reactor-relevant tokamak plasma with strongly negative triangularity (NTR) shaping. Comparison is made for a similar plasma equilibrium, but with positive triangularity (PTR). It is found that the ideal wall stabilization is less efficient for the kink stabilization in the NTR plasma due to a less 'external' eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…It was also found that the wall-stabilization is less effective for NT than PT, leading to a narrow window for RWMs. Otherwise assuming a wall radius of 1.10a for NT and 1.5a for a PT DEMO-size case and using MARS-F and MARS-K, [148] found similar behaviour in terms of ideal/resistive wall, plasma flow and drift kinetic effects due to thermal trapped particles. The lack of wall stabilization depends on the effective eigenfunction.…”
Section: Accepted M Manuscriptmentioning
confidence: 63%
See 1 more Smart Citation
“…It was also found that the wall-stabilization is less effective for NT than PT, leading to a narrow window for RWMs. Otherwise assuming a wall radius of 1.10a for NT and 1.5a for a PT DEMO-size case and using MARS-F and MARS-K, [148] found similar behaviour in terms of ideal/resistive wall, plasma flow and drift kinetic effects due to thermal trapped particles. The lack of wall stabilization depends on the effective eigenfunction.…”
Section: Accepted M Manuscriptmentioning
confidence: 63%
“…RWM with advanced scenario q-profiles are of particular interest for steady-state DEMO-NTT studies. At this stage a detailed comparison between NT and PT plasmas with a "standard" monotonic q-profile was performed in [148]. It was also found that the wall-stabilization is less effective for NT than PT, leading to a narrow window for RWMs.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In particular, it remains an open question on whether and how the internal kink and the associated sawteeth and fishbones behave differently in negative triangularity plasmas as compared to the positive triangularity counterpart. As noted in references [35,36], orbits and the poloidal distribution of trapped particles can significantly differ from those in positive triangularity plasmas. A much larger fraction of trapped particles is populated in the top and bottom of the poloidal cross section, instead of the outboard midplane, in negative triangularity configuration.…”
Section: Introductionmentioning
confidence: 93%
“…The detailed MARS-K formulation is presented in reference [50]. The MARS-K code has been successfully benchmarked against other codes [55,56], and extensively applied to study drift-kinetic effects on the internal kink modes [15,20,27,37,57], and external kink/resistive wall modes [36,50,[58][59][60][61][62][63][64][65] in both positive and negative triangularity plasmas. The hybrid model in the MARS-K code utilizes a pressure-coupling scheme, where the fast-ion drift kinetic effect is coupled to the bulk plasma equation through the pressure tensor in the momentum equation as shown below.…”
Section: Computational Models In Mars-kmentioning
confidence: 99%
“…Наряду с теоретическими и экспериментальными работами в последние годы проведен ряд численных исследований ловушек-галатей. Эти исследования основаны, в первую очередь, на численном решении уравнения Грэда-Шафранова для различных равновесных магнитоплазменных конфигураций (см., например, [2, [37][38][39][40][41][42][43][44][45]). Некоторые численные исследования связаны с моделированием процесса формирования квазиравновесных конфигураций в рамках эволюционных плазмодинамических моделей (см., например, [46]).…”
Section: Introductionunclassified